Rereading Travellers to the East Shaping Identities and Building the Nation in Post-unification Italy - Falcucci, Beatrice; Giusti, Emanuele; Trentacoste, Davide (Connessioni. Studies in Transcultural History, 2022)
Rereading Travellers to the East aims to offer a new perspective on travel literature, the question of nation-building and the history of orientalism. Rereading Travellers focuses on the rereadings to which early modern travel literature about Asia has been subjected by different actors involved in the political, economic, cultural and intellectual life of post-unification Italy. The authors highlight how this literature has been reinterpreted and reused for political and ideological purposes in the context of the formation and reformation of collective identities, from the Risorgimento to the Fascist regime and the early republic. By showing the potential of the notion of rereading, the volume outlines a history of the political and cultural legacy of travel literature which goes well beyond Italy.